Comparison between piezoelectric surgery and conventional saw in sagittal split osteotomies: a systematic review - Silva, L. F. [UNESP]; Carvalho-Reis, E. N.R. [UNESP]; Bonardi, J. P. [UNESP]; de Lima, V. N. [UNESP]; Momesso, G. A.C. [UNESP]; Garcia-Junior, I. R. [UNESP]; Faverani, L. P. [UNESP] (Elsevier, 2017)
A systematic review of the advantages and disadvantages of piezoelectric surgery in comparison with conventional saws for sagittal split osteotomy (SSO) was performed. Relevant studies published in the last 10 years were identified through a search of the PubMed/MEDLINE, Science Direct, and Embase databases and assessed against predetermined eligibility criteria. The initial search resulted in 1736 articles. After applying the inclusion and exclusion criteria, 12 articles remained. A total of 799 patients with an average age of 27.5 years underwent SSO performed using a saw or ultrasonic device. Results showed that it took longer to perform the osteotomies using an ultrasonic device than using a conventional saw. At ≥6 months of follow-up, neurosensory disturbance was seen in 4.7% of patients who underwent piezoelectric surgery versus 61.6% of patients who underwent surgery in which a conventional saw was used. It was found that the use of piezoelectric surgery in SSO leads to the best outcome regarding neurosensory disturbance when compared to conventional saws (P = 0.04) at ≥6 months of follow-up. Further studies are required for the evaluation of the other clinical parameters assessed.
Keywords: orthognathic surgery; osteotomy; piezoelectric surgery; sagittal split ramus